Effect of specimen geometry in tensile Hopkinson bars testing - Ang, Kenneth Woei Meng (2009)
The Spit Hopkinson Pressure Bar (SHPB) apparatus is located in the Strength of Materials Laboratory at the Nanyang Technological University (NTU). There are three common types of SHPB testing techniques. These are tensile, compression and torsion. This report shall focus on tensile SHPB technique.